Análise dos métodos de leira estática e de revolvimento manual na compostagem de resíduos orgânicos gerados em restaurante universitário - Souza, Laís Alves [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Composting is considered a process that enables adding value to organic solid waste turning them into organic fertilizer. In this process, factors such as mishandling the windrow, failed to control the temperature, aeration and moisture content will result in the quality of waste decomposition, and thus affect the quality of the final compound. Decentralized systems such as home composting, composting in restaurants, food courts and schools are one of the solutions for valuing these waste in a non expensive way and with greater quality. For this purpose, the project aims to analyze the conditions for composting of solid waste of the University Restaurant of Rio Claro- SP, through two different composting systems: manual revolving windrow and static pile. It was found that in University Restaurant (RU) on average 33% by weight of the total waste generated in the property are capable of composting. In this sense, in order to investigate the preliminary process operation parameters were mounted one manual windrow composed of 100% of the UR waste and a static pile composed of 60% of the UR waste and 40% of pruning and grass residues (PG). This study analyzed the manual revolving windrow and static pile systems for the parameters: moisture content, pH, C / N ratio and temperature. The study of the proportions of the PG and UR waste pointed to the need for pruning and grass residues addition for composting, considering that the manual revolving windrow composed by 100% of the UR waste had no satisfactory performance due to low temperatures measured during 60 days analysis. The best ratio for manual revolving windrow method analyzed in this study was 60% of the UR waste and 40% of PG waste, in dry weight. From this proportion a static pile was assembled, composed of 60% of UR waste e 40% of PG waste from the maintenance activities of the green area of the university. The biological activity in the static pile reached the maximum temperature of ...

A compostagem é considerada um processo que possibilita agregar valor aos resíduos sólidos orgânicos transformando-os em fertilizante orgânico. Nesse processo, fatores como manejo incorreto da leira, com falhas no controle da temperatura, aeração e teor de umidade irão implicar na qualidade da decomposição dos resíduos, e consequentemente afetará a qualidade do composto final. Sistemas descentralizados como compostagem doméstica, em restaurantes, praças de alimentação e escolas são uma das soluções para valoração destes resíduos de forma não onerosa e com maior qualidade. Com este intuito, o presente projeto visa analisar as condições de compostagem dos resíduos sólidos do Restaurante Universitário da Unesp de Rio Claro- SP por meio de dois diferentes sistemas de compostagem: leira de revolvimento e leira estática. Verificou-se que neste Restaurante Universitário (RU), em média 33% em peso úmido, do total de resíduos gerados no estabelecimento são passíveis de compostagem. Nesse sentido, com a finalidade de investigar preliminarmente os parâmetros operacionais do processo, foram montadas uma leira de revolvimento manual com 100% de resíduos do RU e uma leira estática com 60% de resíduos do RU e 40% de resíduos de poda e capina (PC), proveniente das atividades de manutenção da área verde da universidade. O presente trabalho analisou os sistemas de leira de revolvimento manual e leira estática quanto aos parâmetros: teor de umidade, pH, relação C/N e temperatura. Adicionalmente, foi realizado um estudo sobre as proporções entre resíduos do RU e PC para montagem das leiras, o qual apontou para a necessidade da adição de poda e capina na compostagem, tendo em vista que a leira com 100% de resíduos do RU apresentou comportamento não satisfatório devido às baixas temperaturas aferidas durante os 60 dias de análise. A melhor proporção para o método de leira de revolvimento manual analisadas...
Keywords: Resíduos; Residuos organicos; Reaproveitamento (Sobras, refugos, etc.); Adubos compostos; Restaurantes, bares, etc